Phylogenetic investigation of enteric bovine coronavirus in Ireland reveals partitioning between European and global strains. Issue 1 (December 2015) - Gunn, L.; Collins, P.; O'Connell, M.; O'Shea, H.
Abstract Background Bovine coronavirus is a primary cause of neonatal calf diarrhea worldwide, and is also associated with acute diarrhea in adult cattle during the winter season. There are no reports on molecular characterization of bovine coronavirus in Ireland, and little data exists apart from serological studies. Findings In this study, 11 neonatal (mean age 9 days) calf BCoV strains from the south of Ireland were collected over a one year period and characterized using molecular methods. The spike gene which encodes a protein involved in viral entry, infectivity and immune response shows the most variability amongst the isolates and was subsequently selected for in depth analysis. Phylogenetic analysis of the spike gene revealed that the Irish strains clustered with novel BCoV strains from Europe in a unique clade, possibly indicating lineage partitioning. Direct analysis of alignments identified amino acid changes in the spike protein unique to the Irish clade. Conclusion Thus, monitoring of bovine coronavirus in Ireland is important as the current isolates in circulation in the south of Ireland may be diverging from the available vaccine strain, which may have implications regarding future BCoV vaccine efficacy.